Bangladesh : past and present - Ahmed, Salahuddin (New Delhi : A.P.H. Pub. Corp., 2004)
"This work is an attempt to unfold the contribution made by the great Muslim Bengalis in the independence movement of India and later in the struggle for autonomy of East Pakistan culminating in the independence of Bangladesh. I have analysed the events of the post-independence period of Bangladesh and the challenges encountered by the new nation as it enters the year 2003"--P. viii.
Includes bibliographical references (p. 349-359) and index.
Keywords: Muslims -- Bangladesh; Bangladesh -- History